Implementation of the “Bhabinkamtibmas Melali” Police Resort Tabanan Program as an Effort to Improve Public Services to Implement the Reform of the Police Bureaucracy and Good Governance - Picha Armedi; Pantius Drahen Soeling (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The maintenance of public security and order as well as providing protection, shelter, and services to the community are tasks carried out by the Indonesian National Police or the Indonesian National Police. Its function as a protector, protector and public servant of the POLRI is manifested in bureaucratic reform as a form of POLRI's efforts to increase public trust and lead to good governance. In formulating a strategy for serving the community, various efforts have been made by the POLRI. One of them is a program created by the Tabanan Resort Police, namely "Bhabinkamtibmas Melali". Through this program, it is hoped that the Indonesian National Police or POLRI can improve the quality of service to the community so that they gain public trust in carrying out their duties. Analytical descriptive research is applied in this case. This study found that the "Bhabinkamtibmas Melali" program carried out by the Tabanan Resort Police had been implemented well and overall received a good response from the community.